Gambaran Kepatuhan Diet dan Gula Darah Puasa pada Pasien Diabetes Tipe II - Wulandari, Novita Kurnia; Mardiyono, Mardiyono; Rahayu, Umi Margi (Prodi Keperawatan Purwokerto, 2024)
Background: Type 2 diabetes mellitus is a metabolic disorder in which the body does not produce enough insulin or the glucose level in the blood exceeds the normal limit, which is 130 mg/dL for fasting blood sugar levels. There are 4 pillars of management of type 2 diabetes mellitus, including nutrient therapy and pharmacology. Diabetic patients can apply nutrient therapy by adjusting the diet with the 3J principles (amount, schedule, and type). Pharmacological therapy can be carried out by routinely taking antidiabetic drugs according to the recommended dosage. Objective: The aim of the study was to describe dietary compliance and fasting blood sugar levels in people with Type 2 Diabetes Mellitus. Method: This type of research is a quantitative pre-experimental study with one group pre-test-post-test design, with 34 using a purposive sampling method. The instrument in this study used MMAS-8. Result: The results of the univariate analysis showed that most of the research respondents were women (55.9%) with an age range of 61-70 years (64.7%), last education level was high school (47.1%), privately owned employees (55.9%), and duration of suffering from DM 5 years (100%). Conclusion: A significant relationship exists between diet adherence and fasting blood sugar levels in patients with type 2 diabetes mellitus. Conclusion: Based on this research, it is expected that people with type 2 diabetes mellitus can apply a good diet pattern and regularly consume anti-diabetic drugs according to the recommendations of health workers.